Adult obesity: Decomposition analysis socio-economic determinants of adult obesity: Decomposition analysis on Turkey - (:unkn) unknown (Peter Lang AG, 2019)
Obesity is an essential and growing public health problem worldwide, and obesity growth rates are high in both developed and developing countries. Individuals with lower socio-economic status are more likely to be exposed to risk of obesity than their counterparts. We believe that socio-economic status-related inequalities in obesity have various factors and addressing these inequalities requires coordinated public policies. In this respect, the aim of this chapter is to disentangle and decompose the socio-economic determinants of adult obesity in Turkey. We perform the empirical analysis using Turkish Health Survey data set prepared by Turkish Statistical Institute (TURKSTAT) for the years 2014 and 2016. We conduct the analysis separately for males and females. We estimate the concentration indices to find the extent of socio-economic inequalities in obesity. Negative concentration indices show prevalence of obesity is higher among those with relatively low socio-economic status. Furthermore, we apply Fairlie decomposition analysis to determine the determinants of inequality in obesity. Fairlie decomposition results suggest that the probability of obesity is approximately 30 % for low-educated individuals and 15 % for the others. The difference between two groups indicates the degree of contribution of other factors to inequality in obesity. Decomposition results show that age, gender and certain chronic illnesses make the highest contribution to inequality in obesity. © Peter Lang AG 2019.
Keywords: Concentration index; Decomposition; Obesity; Socio-economic status